2020
DOI: 10.1093/mnras/staa2519
|View full text |Cite
|
Sign up to set email alerts
|

A dusty origin for the correlation between protoplanetary disc accretion rates and dust masses

Abstract: Recent observations have uncovered a correlation between the accretion rates (measured from the UV continuum excess) of protoplanetary discs and their masses inferred from observations of the sub-mm continuum. While viscous evolution models predict such a correlation, the predicted values are in tension with data obtained from the Lupus and Upper Scorpius star forming regions; for example, they underpredict the scatter in accretion rates, particularly in older regions. Here we argue that since the sub-mm obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 95 publications
(197 reference statements)
6
48
0
Order By: Relevance
“…Recently, the connection of measurements ofṀ acc from spectroscopy and of disk masses with millimeter interferometry, mainly with the Atacama Large Millimeter/submillimeter Array (ALMA), has also revealed the presence of a correlation between these two quantities (e.g., Manara et al 2016b;Mulders et al 2017), which is possibly in line with expectations drawn from viscous evolution (e.g., Jones et al 2012;Lodato et al 2017;Rosotti et al 2017), but this also reveals tensions with respect to this simplified description of disk evolution (e.g., Mulders et al 2017;Manara et al 2020). These tensions may be relieved by introducing complications to a simplistic model, including external or internal photoevaporation (e.g., Rosotti et al 2017;Sellek et al 2020a;Somigliana et al 2020), or dust evolution (Sellek et al 2020b).…”
Section: Introductionsupporting
confidence: 71%
“…Recently, the connection of measurements ofṀ acc from spectroscopy and of disk masses with millimeter interferometry, mainly with the Atacama Large Millimeter/submillimeter Array (ALMA), has also revealed the presence of a correlation between these two quantities (e.g., Manara et al 2016b;Mulders et al 2017), which is possibly in line with expectations drawn from viscous evolution (e.g., Jones et al 2012;Lodato et al 2017;Rosotti et al 2017), but this also reveals tensions with respect to this simplified description of disk evolution (e.g., Mulders et al 2017;Manara et al 2020). These tensions may be relieved by introducing complications to a simplistic model, including external or internal photoevaporation (e.g., Rosotti et al 2017;Sellek et al 2020a;Somigliana et al 2020), or dust evolution (Sellek et al 2020b).…”
Section: Introductionsupporting
confidence: 71%
“…Because only the grains larger than the wavelength have significant opacity to be observed, the physics of grain growth and drift is fundamental in setting the observed disc size. Moreover, Sellek et al (2020) show that smooth models including radial drift can also explain the distribution of observations in the accretion rate -disc mass plane, even in the old Upper Sco region.…”
Section: Introductionmentioning
confidence: 80%
“…Indeed, in this case, the disc radius after 3 Myr is very similar to the initial value, implying a strong dependence on the initial conditions of protoplanetary discs and no disc evolution: initially large discs remains large while initially compact discs are observed with small dust radii. Moreover, Sellek et al 2020 found that the resulting dust mass of the discs are proportional to 𝑓 grow , so that a large reduction in growth efficiency also corresponds to a correspondingly large increase in dust mass: that would help to explain the observed large masses of a few discs in Lupus, but the bulk of the population would be too massive compared to observations.…”
Section: Dust Evolution: a Slower Growth?mentioning
confidence: 94%
See 2 more Smart Citations